The development of systematic thought in early Mālikī jurisprudence, 8th-9th Centuries A.D. - Gledhill, P (2014)
By the eleventh century, the conduct of jurisprudence in the Mālikī school of law – one of four that would survive in Sunni Islam – was predicated on a legal system that comprised a particular set of sources: mainly, the positive legal rules posited by Mālik b. Anas (d. 179/795) and a few of his subsequent adherents, and ḥadīth and Qur᾽an. The structure of the legal system was one in which these sources were conceived to cohere analogically. By analogy, they could be correlated to each other and thereby systematically rationalized, and new rules to govern new cases generated from, and added to, them. This study recovers the antecedents of that system and describes the main stages of the process by which Mālikī jurisprudence acquired the systematic character of its classical form. It provides a re-assessment of Mālik’s own jurisprudence and of the role of precedent and ḥadīth in the Medinese tradition, arguing that the origins of systematic thought in the Mālikī tradition are to be sought in Mālik’s retrospective rationalizations by analogy of rules pronounced nonetheless from arbitrary considerations. I distinguish the mode of analogy that Mālik employed to this effect (tashbīh) from that which his Iraqi contemporaries and the later classical schools employed ostensibly to derive rules from sources ab initio (qiyās). Mālik, I contend, in fact opposed qiyās because it threatened to undermine the sufficiency of juristic discretion by imposing systematic constraints on the personal reasoning of authoritative arbiters. I show how subsequently the Mudawwanah, a work compiled by Mālik’s ninth-century followers in the Islamic West, promoted the formation of a legal system by subjecting Mālik’s teaching and his students’ ramifications of it to a Ḥanafite design by which they became susceptible of analysis along analogical lines. The system implicit in the Mudawwanah is structurally but not yet materially classical. It remained for the Western Mālikīyah, through their encounters in the East with Shāfi῾ite legal theory in the later tenth century, to absorb into the fabric of their system, which so far comprised only the positive rules of the tradition itself, the revealed sources from which, by qiyās, al-Shāfi῾ī (d. 204/820) in the early ninth century had insisted the law be derived. As background to this theory of systematization, I also address inter alia the following questions, which bear in one way or another on our appreciation of Mālik’s jurisprudence and/or the extent to which we may suppose it to be accessible in the recensions of the Muwaṭṭa᾽: the transmission of the vulgate in ninth-century Andalus; the reception of Mālik’s doctrine in Iraq (as perceived through the Muwaṭṭa᾽ of al-Shaybānī – in particular, the editorial principles that informed its composition – and the Ḥujjah ῾alá ahl al-Madīnah); other recensions and the possibilities for a chronology of Muwaṭṭa᾽āt; representation of Mālik’s doctrine in the Ikhtilāf Mālik wa-al-Shāfi῾ī; the way in which Mālik transmitted the Muwaṭṭa᾽ as an explanation of variation between its recensions.